Pengaruh Faktor Internal dan Eksternal Pada Audit Delay (Studi Empiris pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Herry Goenawan Soedarsa; Nurdiawansyah NURDIAWANSYAH (Jurnal Akuntansi dan Keuangan, 2017)
This study aims to determine and analyze the effect of firm size, profitability, solvency, auditor quality, and auditor opinion on audit delay on food and beverage companies listed on Indonesia Stock Exchange period 2013-2015. The first hypothesis proposed is firm size positively influence audit delay, second hypothesis is profitability negatively affect audit delay, third hypothesis is solvency have positive effect to audit delay, fourth hypothesis is auditor quality have negative effect to audit delay, hypothesis fifth is auditor opinion negatively affect audit delay. Audit delay measurement is based on the period between the closing date of the financial year to the date of opinion on the independent auditor's report. The sample in this research is food and beverage company listed in Indonesia Stock Exchange year 2013-2015. Sampling using purposive sampling to obtain the number of samples of 30 food and beverage companies that meet the criteria of the research sample that has been determined. Firm size measured by total asset, profitability measured by Return on Asset (ROA), solvency measured using Debt Equity Ratio (DER), auditor quality and auditor opinion measured using dummy variable. Data analysis technique is done with classical assumption test, hypothesis test using multiple linear regression analysis with SPSS 18.0 for windows. The results showed that partially firm size, profitability, solvency and auditor quality have negative effect on audit delay in food and beverage companies listed on Indonesia Stock Exchange while the auditor's opinion variable positively influence to audit delay at food and beverage company listed in Bursa Indonesia Securities.